Website-Based Baiturrahman Mosque Management Information System Case Study Of Baiturrahman Mosque Pandu Raya - Riswandha Imawan; Puspa Eosina; Dewi Primasari (Universitas Ibn Khaldun Bogor, 2025)
The Baiturrahman Mosque is a place for Muslims to gather to perform prayers or other Islamic activities based on the Shari'a and adab in it. These activities cannot be separated from the existence of administrators from each mosque, tasked with conveying information about activities at the mosque. the purpose of this research is to design and build a website-based management information system for the Baiturrahman mosque. The waterfall model is a system development model that is systematic and sequential in building software. Building a website-based mosque management information system. From the Baiturrahman mosque information system, there are several menus that local worshipers can use, such as qurban savings, information about mosque activities and finances.